2005
DOI: 10.1039/b504396b
|View full text |Cite
|
Sign up to set email alerts
|

Use of PFU protozoan community structural and functional characteristics in assessment of water quality in a large, highly polluted freshwater lake in China

Abstract: Structural and functional parameters of protozoan communities colonizing on PFU (polyurethane foam unit) artificial substrate were assessed as indicators of water quality in the Chaohu Lake, a large, shallow and highly polluted freshwater lake in China. Protozoan communities were sampled 1, 3, 6, 9 and 14 days after exposure of PFU artificial substrate in the lake during October 2003. Four study stations with the different water quality gradient changes along the lake were distinguishable in terms of differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 16 publications
4
45
0
Order By: Relevance
“…6) during both seasons. The higher population density results in higher organic contaminant discharge, such as food waste, human sewage and industrial wastes, which contribute to increased COD concentrations (Xu et al, 2005;Campos et al, 2012;Mohseni-Bandpei and Yousefi, 2013;Sivri et al, 2014). …”
Section: Interpretation Of Water Quality and Predicting Variablesmentioning
confidence: 99%
“…6) during both seasons. The higher population density results in higher organic contaminant discharge, such as food waste, human sewage and industrial wastes, which contribute to increased COD concentrations (Xu et al, 2005;Campos et al, 2012;Mohseni-Bandpei and Yousefi, 2013;Sivri et al, 2014). …”
Section: Interpretation Of Water Quality and Predicting Variablesmentioning
confidence: 99%
“…PFU microbial communities have been shown to form complex species assemblages, which exhibit many of the characteristics of structural communities (Xu et al, 2005). Various structural and functional characteristics of PFU microbial communities have been tested to be correlated with the degree of the lake's eutrophication (Cairns and McCormick, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the functional parameters were utilized effectively in assessing the water quality (Xu et al 2005). Among the three functional parameters, the S eq is a sensitive parameter to confirm pollution levels, which is negatively correlated with the concentrations of pollutants (Shen et al 1990).…”
Section: Discussionmentioning
confidence: 99%